FENOMENA PRAGMATIS DALAM AL-QUR’AN: ANALISIS TINDAK TUTUR ILOKUSI PADA PERCAKAPAN MUSA A.S. DAN KHIDIR - Rizza Faesal Awaludin; Ika Wahyu Susiani (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2020)
The studies of Qur’an have been carried out by many researchers, including studies conducted on the story of Khidir with the prophet Moses peace be upon him. However, none of the studies specifically examined it through pragmatic review. This research aims to reveal the types of ilocutionary act contained in the conversation between the prophet Musa and Khidir. This research uses a qualitative approach that is descriptive through a literature review. Analysis of the conversation between the prophet Moses peace be upon him and Khidir reveals the existence of three types of ilocutionary act, directive (ask, demand, plead, and suggest), commisive (promise and offer), and declarative (determine and give punishment). With the disclosure of these types of ilocutionary act, it is expected to provide a new perspective in looking at the friendship story of the two righteous servants of Allah.